Equivalente esférico e valores da espessura da camada de fibras nervosas obtidas com o GDX TM Scanning Laser System® - Alvarenga, Lênio Souza [UNIFESP] (1999)
Purpose: To evaluate the effect of spherical equivalent on the acquisition of nerve fiber layer (NFL) thickness with GDX TM Scanning Laser System®. Methods: Forty-one eyes of 41 volunteers were enrolled in this study. All of them presented with no ocular disease and no visual field defect. The NFL thickness was measured with GDX TM Scanning Laser System® as described in its manual. The values obtained in a group of volunteers with negative spherical equivalent (group I) were compared to those from a group with a positive spherical equivalent (group II) by the Mann-Whitney test. Results: There was no statistical difference between mea-surements in eyes of group I and those in group II. The NFL thickness measurements were not correlated with the sphe-rical equivalent. Conclusions: In the studied group there was no statistical difference in the GDX TM Scanning Laser System® parameters related to spherical equivalent.